Resistance of calves to Cryptosporidium parvum: effects of age and previous exposure. - Harp, J A (1990)
Cryptosporidium parvum is a coccidian parasite that causes diarrheal disease in many vertebrate species, including young (less than or equal to 1 month old) calves. Older calves and adult cattle are resistant to infection. In this study, newborn calves were raised in isolation from C. parvum for 1 week to 3 months before experimental challenge with the parasite. Calves orally challenged with C. parvum at 1 week of age shed oocysts in their feces and had diarrhea after challenge exposure. When these calves were rechallenged at 1 and 3 months of age, they neither shed oocysts nor had diarrhea. There was no significant increase in the mean anticryptosporidium enzyme-linked immunosorbent assay serum antibody titer in these calves following any of the challenge exposures. Calves orally inoculated with C. parvum for the first time at 1 month of age shed oocysts, had diarrhea after challenge exposure, and were resistant to rechallenge at 3 months of age. These calves had a twofold increase in serum antibody titer after the first challenge and no increase after the second challenge. Calves orally inoculated with C. parvum for the first time at 3 months of age shed oocysts, and two of seven animals had diarrhea. These calves had a 10-fold increase in serum antibody to C. parvum after exposure. This study demonstrates that calves raised in isolation from C. parvum remain susceptible to challenge until at least 3 months of age. Furthermore, within this time period, initial exposure and recovery renders calves resistant to further challenge with the parasite. The data also suggest that exposure of young calves to C. parvum may inhibit the development of a serum antibody response to the parasite.